(untitled) (American Journal of Business Management, Economics and Banking, 2026)
The audit of accounts payable is considered one of the most important areas of modern auditing because accounts payable directly influence the liquidity, financial stability, and reliability of corporate financial reporting. In the context of globalization, increasing business transactions, and expanding credit relationships, enterprises face significant risks associated with the recognition, valuation, and disclosure of liabilities. This article investigates theoretical and practical issues related to the audit of accounts payable based on International Standards on Auditing (ISA) and International Financial Reporting Standards (IFRS). The study examines the international and national relevance of accounts payable auditing using statistical indicators and analytical data. Furthermore, the literature review summarizes the scientific views of foreign and local scholars regarding the methodology and significance of accounts payable auditing. The analysis and results section evaluates current auditing procedures, risk-oriented audit approaches, analytical procedures, and digital technologies used in accounts payable auditing. Particular attention is paid to detecting hidden liabilities, preventing fraudulent reporting, and improving internal control mechanisms. The study concludes that improving accounts payable auditing contributes to enhancing the reliability of financial statements, strengthening investor confidence, and ensuring effective corporate governance. The findings of this research may serve as a scientific and methodological basis for auditors, accounting specialists, researchers, and higher educational institutions in improving liability auditing methodologies under modern economic conditions.